Physiological indices and the yield of genotypes of sugarcane in the handling of drought and drip irrigation - Arlanch, Adolfo Bergamo [UNESP]; Gava, GLauber José De Castro; Kölln, Oriel Tiago; Dellabiglia, William José; Scarpare, Fabio Vale; Pires, Regina Celia De Matos (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
The objective of this work was to use physiological indices and yield of stalks and sugar of different genotypes in two contrasting water managements: irrigated and dry land management, to identify genotypes tolerant to water deficiency and responsive to irrigation. The experiment was developed at Hélio de Morais Research Unit in Jaú/SP, Brazil, from the Agronomic Institute of Campinas (IAC-Jaú). The experimental design was completely randomized block with four replications made up of the combination of four sugarcane genotypes: RB867515, SP801842, CTC 6, RB92579 and two crop managements: underground drip irrigation management and dry. During the development of the experiment, the physiological indexes were evaluated: stomatal conductance, leaf temperature, estimated apparent chlorophyll content (SPAD) and leaf area index (IAF). At the end of the experimental period the yield of stalks and sugar were quantified. The physiological indices: stomatal conductance (gs) and leaf temperature, selected with greater accuracy, sugarcane genotypes tolerant to water deficiency and responsive to irrigation technologies. The genotypes RB92579 and CTC6 were less tolerant to water deficit compared to genotypes RB867515 and SP80-1842, considering the yield of stalks and sugar.
Índices fisiológicos e a produtividade de genótipos de cana-de-açúcar nos manejos de sequeiro e irrigado por gotejamento
Keywords: Leaf temperature; Saccharum spp; SPAD; Stomatal conductance; Subsurface drip irrigation